Getting to Know You: Motivating Cross-Understanding for Improved Team and Individual Performance - Janardhanan, Niranjan S.; Lewis, Kyle; Reger, Rhonda K.; Stevens, Cynthia K. (Organization Science, 2020)
Many contemporary organizations depend on team-based organizing to achieve high performance, innovate services and products, and adapt to environmental turbulence. Significant research focuses on understanding how teams develop, assimilate, and apply diverse information; yet, organizational practices have evolved in new ways that are not fully explored in the teams literature. Individuals with diverse motivations, knowledge, and perspectives are often assigned to teams, creating burdens for members to develop effective ways to work together, learn from each other, and achieve goals amid the complexity of today’s organizational contexts. In this paper, we examine a multilevel model of how team goal orientation affects cross-understanding—the extent to which team members understand the other members’ mental models—which in turn, affects team and individual performance. We examine these effects using 160 teams of 859 participants who completed a semester-long business simulation. Findings show that the more team members are motivated by learning goals, the greater a team’s cross-understanding and subsequent team and individual performance. These effects are dampened when members are motivated by performance goals—to avoid mistakes or prove competence. This study expands the cross-understanding literature, revealing motivational antecedents that explain why some teams develop higher cross-understanding than others. We also contribute to the goal orientation literature by demonstrating that team goal orientation influences members’ learning about other members and in so doing, also affects team and individual performance. Because team motivation can be influenced by organizational practices, our findings also contribute practical insights for organizational leaders.